Determination of lymphocyte subjects in patients with major depressive disorder (MDD) - Sanusi, Siti Nor Fairus Mohamed (2018)
Major depressive disorder (MDD) has been associated with dysregulation of immune system. While many studies on activation of innate immune response currently dominates the research area, the dysregulation in adaptive immune system especially in circulating lymphocyte subsets has rarely been explored. Some studies indicated that the severity of MDD is important with respect to the extent of the immune changes in MDD patients. The objective of this study was to determine the predisposing factors of MDD and the common symptoms in MDD patients based on Beck Depression Inventory (BDI) and Montgomery-Asberg Depression Rating Scale (MADRS), and to determine the percentage and absolute count of lymphocyte subsets in MDD patients and their comparison between different severity of the disease. This study involved 47 MDD patients recruited from Psychiatric Clinic, Hospital Universiti Sains Malaysia (HUSM) and 47 healthy controls. MDD patients were diagnosed according to Diagnostic and Statistical Manual of Mental Disorders Fifth Edition (DSM-V) criteria. The symptoms and severity of MDD was assessed using BDI and MADRS scale. The percentage and absolute count of CD4+ T cells, CD8+ T cell, CD4+ CD25+ Tregs, CD4+ CD25+ Foxp3+ Tregs, CD16+ CD56+ NK cells and CD19+ B cells were determined by using immunophenotyping technique. Mann-Whitney test was used to compare the percentage and absolute count of lymphocyte subsets between MDD patients and healthy controls. Kruskal-Wallis test was used to compare the percentage and absolute count of lymphocyte subsets between different severity of MDD. The results showed that those married, smoker, possess lower educational level and living in rural area have higher risk for MDD. Based on BDI, the most common symptoms reported by our MDD patients were fatigue and irritability. While based on MADRS, MDD patients also have inner tension, concentration difficulties, inability to feel and pessimistic thought. This study showed that there were no significant differences in the percentage and absolute count of CD4+ T cells (p=0.148; p=0.190), CD8+ T cells (p=0.316; p=0.783), CD16+ CD56+ NK cells (p=0.731; p=0.530), and CD19+ B cells (p=0.136; p=0.148) between MDD patients and healthy controls. However, we found a significatly higher percentage and absolute count of CD4+ CD25+ Tregs (p<0.001) and CD4+ CD25+ Foxp3+ Treg cells (p=0.003; p=0.001) in MDD patients compared with healthy controls. This study also showed that there were no significant differences in the percentage and absolute count of lymphocyte subsets between mild, moderate and severe MDD patients.